Pengaruh Sistem Pengendalian Internal Terhadap Persediaan Barang: Studi pada salah satu perusahaan retail di Kota Bandung - Wajib Ginting (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
This research departs from identifying problems that occur, which indicate a gap in the inventory of goods. This study aims to determine the effect of the internal control system on the inventory of goods. The research method used is quantitative research methods with simple regression analysis techniques carried out at one of the retail companies in Bandung. The results showed a significant effect of the internal control system on the inventory of goods. The results of this study recommend that the company further improve its internal control system.